(3MdjI GdYQhS hHSW GdfahSs - (3CMeO GdSfGfs
(3ChdgG (B:s
(3hHYO ajbhd Efi deG QCjJ Cf CTQa GdQjGVjGJ GdYde GdeYQha HYde GdehSjbi s
(3BNQgG (B:s
(3hdeG MGQHfG ddEbdGY Yf Whd GdcdGe hGQOfG GdGNJUGQ s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3afhf LejdI (B622) s
Keywords: (3GdehSjbi hGdZfGAs